Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Biologi di MAN 2 Kota Cirebon - Endang Suhaeni (Jurnal Pendidikan Madrasah, 2022)
This study aims to determine the application of the Student Team Achievement Division (STAD) type of cooperative learning model in improving Biology learning outcomes in the material "describing the characteristics of viruses, replication and their role in life." This research is an action research, conducted in two cycles including planning, implementation, observation, and reflection activities. The subject of the study was a class X MIA MAN 2 student in Cirebon City. The results showed that the average score of learning outcomes in cycle I of 62.5% increased to 87.5% in cycle II. The Student Team Achievement Division (STAD) type of cooperative learning model can be applied in the learning process to students at the Madrasah Aliyah level.